Mulheres em foco : uma análise das eleições brasileiras em 2010 - Borges, Lucelia (2012)
The research object of this dissertation is the femininesubrepresentation phenomenon in the institutionalized politic system in Brazil. The discussion about the genre theme has beenaroused in the country on account of the last presidential election, which has counted on two candidates, both with great chances of winning. Considering the election period a rich period of materials production for analysis and discussions on the groupssubrepresentation theme, it has been thought about the inequality related to the access and success in the exercise of the power between men and women. It is undertaken an analysis of express conceptions by the individuals about the feminine subrepresentation theme during the discussions offered by Politic Culture, genre and elections running at State University of Maringa, which, during the election period of 2010, organized focused groups with maringaensevoters with the main objective of discussing the participation of women in the politics world.